Creative confidence unleahing the creative potential within us all - Kelly, Tom; Kelly, David (London William Collins, 2013)
oo often, companies and individuals assume that creativity and innovation are the domain of the "creative types." But two of the foremost experts in innovation, design and creativity on the planet show us that each and every one of us is creative. In an incredibly entertaining and inspiring narrtiave that draws on countless stories from their work at IDEO and with many of the world's top companies and design firms, David and Tom Kelley identify the principles and strategies that will allow us to tap into our creative potential in our work lives, and in our personal lives, allow us to think outside the box in terms of how we approach and solve problems. It is a book that will help each of us be more productive and successful in our lives and in our careers